Children’s Information Seeking Behavior: A Laboratory Versus an Operational Research Environment - Large, Andrew; Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper explores the issues involved in conducting research into the information-seeking behavior of young users in an educational context, and in particular discusses the relative merits of an experimental (in vitro) research environment compared with an operational (in vivo) environment. Research papers typically concentrate on the results generated by the adopted methodology. . .